Supporting the Sustainable Energy Transition in the Canary Islands: Simulation and Optimization of Multiple Energy System Layouts and Economic Scenarios - Barone, Giovanni; Buonomano, Annamaria; Forzano, Cesare; Giuzio, Giovanni Francesco; Palombo, Adolfo (Frontiers in Sustainable Cities, 2021)
The Canary Islands have great potential for the implementation of sustainable energy systems due to its availability of natural resources. The archipelago is not connected to the mainland electricity grid and the current generation system is mainly based on traditional fossil fuel. Therefore, the islands strongly dependent on fuel importations, with high costs due to logistics. Furthermore, due to the inadequate coverage of residential heating and cooling needs, the per capita energy consumption is far below the Spanish national average. This occurrence has inspired an intense debate on the current development model of the Canary Archipelago, which has led to the implementation of actions and measures aimed at achieving greater energy sustainability in the archipelago. Furthermore, at a local scale, an important investment plan has been carried out by the Spanish grid operator to ensure energy supply, to improve the system security and reliability, and to optimize the integration of renewable energies. Future measures and investments will be crucial to ensure a sustainable growth, both from the economic and the environment point of views. In this framework, this paper aims to discuss and compare the energy solutions, based on renewable energy technologies, identified to boost the sustainable transition of the islands. To this aim, multiple configurations of a wind power plant coupled with reversible hydro power/storage system for the distributed and on-site energy production in the island of Gran Canaria have been modelled, simulated, and optimized by a TRNSYS/Matlab algorithm suitably developed. Specifically, along with the proposed system layouts, different scenarios related to diverse annual costs growth rate of fuel have been investigated. The proposed analysis covers a time horizon of 20 years, up to 2040, and aims at assessing the impact of the investigated solution on energy demand, energy supply, and population incomes. The analysis demonstrates the importance of investments targeted at the implementation of renewables. The proposed scenarios indicate that the current energy model has the potential to a radical change and to tackle climate change and energy issues while producing substantial economic savings and better life conditions for the population in the next years.